METHODOLOGICAL PROBLEMS OF RELIGIOUS STUDIES IN SPACE INFORMATION SOCIETY - Конотоп, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article analyzes the theoretical and methodological problems of modern religion. We consider such issues as religious formation, the ratio of subject and object and others. The conclusion is that religion is a complex science, it includes historical, anthropological, sociological, ethnographic, psychological, and others knowledge about religion.